A new genus of bamboo coral (Octocorallia: Isididae) from the Bahamas - Watling, Les (Zootaxa, 2015)
A bamboo coral collected during a deep-sea expedition to the Bahamas in 2009 proved to have a unique combination of features for a member of the bamboo coral subfamily Keratoisidinae: the structure and shape of the polyps, the sclerites consisting entirely of rods, some of which extend the length of the polyp, the delicateness of the branches with solid internodes, and the deep funnel construction of the peristomal region into which the tentacles can contract. The specimens are described as a new genus and species.